Real Christianity contrasted with the prevailing religious system - Wilberforce, William, 1759-1833; Houston, James Macintosh, 1922- (Portland , OR Multnomah, 1982)
Based on the American edition of 1829...a practical view of the prevailing religious system of professed Christians, in the higher and middle classes.
Keywords: Christianity -- essence, genius, nature; Apologetics -- 18th century